An introduction to Catholicism - Cunningham, Lawrence (Introduction to religion, 2009)
The beliefs and practices shared by one billion Catholics around the globe form the focus of this essential textbook. It guides the student through the complex, diverse world of 21st-century Catholicism, explaining doctrinal formulas, institutional structures and patterns of life and worship as evolving responses to historical and social contexts.